Respuesta :

Answer: 16

Step-by-step explanation:

[tex](g \circ f)(-6)=g(f(-6))\\\\f(-6)=-(-6)-2=4\\\\\implies g(f(-6))=g(4)=4^2 = \boxed{16}[/tex]

The value of the function estimation; (g°f)(-6) is; 64.

What is the value of the function estimation?

It follows from the task content that; the fumcti given are; f(x) = -x-2 and g (x) =x².

Hence, the function (g°f) (x) can be evaluated as; (-x-2)² = x² +4x +4.

Ultimately, when x = 6; (g°f)(-6) = 6² +4(6) +4 = 64.

Read more on functions;

https://brainly.com/question/20384115

#SPJ1